Dining House Information System (Case Study: Tengku Di Ujung, Simeulue District) - Ayat Hasanul Alfarisi (International Journal Software Engineering and Computer Science (IJSECS), 2021)
The Tengku Diujung restaurant is one of the tourist destinations that is frequently visited by tourists because the restaurant has a mainstay menu that is in demand by many visitors, one of which is lobster noodles. However, each sales report still records data manually, sometimes experiencing errors due to inaccuracies in recording data. The formulations in this study are; how to manage all data on reports of receipts, orders, and sales or expenditures of goods, and whether employees are easy to find data, and how to manage data on receipts, orders, and sales or expenditures of goods. To complete the data needed in the preparation of this study, the authors use writing sources, namely; Library Research, Field Research, and Interviews and Observatories. From the results of the discussion on "Inventory Information System at the Tengku Diujung Restaurant (Simeulue Regency)" the author can conclude that the use of a manual system has limitations in selling goods. This information system, makes it easier for the restaurant to present information about revenue, ordering, and sales data to its customers. Although it requires a lot of money, it is worth the ease with which it is obtained, and designing this application will speed up the production of receipts, orders, and sales reports. The results of this study are the development of an Inventory Information System application with 9 (nine) inputs in the form of; data on goods, suppliers, customers, receipts, expenses, stocks, transactions, and application users. There are 6 (six) output designs consisting of; goods data, suppliers, customers, receipts, expenses, and stock reports.